Analisis Dampak Game Online terhadap Kurangnya Komunikasi dalam Meningkatkan Kosentrasi Belajar di Kelas - Siti Apriani; A Arianto; AF Sonny (MUKASI: Jurnal Ilmu Komunikasi, 2025)
In the world of education, technological developments are sometimes misused by teenagers. One factor that occurs in the field is the phenomenon of excessive use of online games, which can affect communication between teachers and students, which can increase concentration in learning at SMA Negeri 4 Takalar. This research is a field study (field research) which is a study conducted systematically with the existing data conditions in the field. The method used in this study uses qualitative research with a phenomenological approach, research data collection techniques using observation, interviews, and documentation techniques. The results of field research with qualitative methods provide a result where the excessive use of online games can disrupt communication between teachers and students and even communication between students. Online game playing not only affects communication but the level of student concentration in class has decreased because rest time at home, especially at night, is used to play online games so that when in class and during learning, there are students who are sleepy and lack focus when asked questions related to learning. Student learning concentration is a form of concentration of thought or attention in order to be able to understand the material presented and put aside anything that interferes with the learning process. Innovation is needed in learning to overcome this phenomenon, one of which is using media or creating learning such as games so that students do not get bored in the learning process in class.